Factors Affecting Mortality in People Living with HIV with Antiretroviral Therapy: A Meta-Analysis - Fauziah Shinta Anindita; Fenita Indriani; Bhisma Murti; Nindita Arum Veibiani (Journal of Epidemiology and Public Health, 2024)
Background: TB is the leading cause of death among people living with HIV. In 2020, an estimated 214,000 people living with HIV died from TB. People with AIDS have a severely damaged immune system. They are increasingly suffering from severe diseases, called opportunistic infections (OI). This study aims to analyze and estimate the influence of gender, TB Coinfection, Opportunistic Infection on mortality in ODHIV with Antiretroviral Therapy.Subjects and Method: Systematic review and meta-analysis using PRISMA flowchart and the PICO model. Population: ODHIV with ART. Intervention: Women, Co-infected TB, Opportunistic Infections. Comparison: Male, no co-infected TB, no Opportunistic Infection. Outcome: Mortality Article search using Google Scholar, PubMed and Science Direct databases. The keywods used include "HAART" or "HIV" or "HIV/AIDS" and "Gender" and "TB Coinfections" or "TB" and "Opportunistic Infections" and "Mortality" and "Antiretroviral Treatment". The 17 included articles are fulltext in English with a cohort design study from 2008 to 2023 and report on the Hazard Ratio in a multivariate analysis. Data analysis using the RevMan 5.3 application.Results: A total of 17 cohort studies involving 23,651 research subjects from Vietnam, China, Japan, Ethiopia, and South Africa. The data collected showed that female ODHIV had a mortality risk of 0.7 times compared to male ODHIV (aHR= 0.70; CI 95%=0.60 to 0.79; p<0.001). In ODHIV with coinfected TB has a mortality risk of 1.86 times compared to ODHIV without coinfected TB (aHR= 1.89; CI 95%=1.36 to 2.61; p<0.001). ODHIV with Opportunistic Infection has a 1.90-fold risk of mortality compared to ODHIV without Opportunistic Infection (aHR= 1.90; CI 95%=1.50 to 2.42; p<0.001).Conclusion: Female gender decreases the risk of mortality, while TB coinfection and Opportunistic infection increase the risk of mortality in ODHIV with Antiretroviral Therapy.